A Size‐Reducible Nanodrug with an Aggregation‐Enhanced Photodynamic Effect for Deep Chemo‐Photodynamic Therapy. (1st August 2018) - Ji, Chendong; Gao, Qin; Dong, Xinghua; Yin, Wenyan; Gu, Zhanjun; Gan, Zhihua; Zhao, Yuliang; Yin, Meizhen
Abstract: Fluorescent dyes with multi‐functionality are of great interest for photo‐based cancer theranostics. However, their low singlet oxygen quantum yield impedes their potential applications for photodynamic therapy (PDT). Now, a molecular self‐assembly strategy is presented for a nanodrug with a remarkably enhanced photodynamic effect based on a dye‐chemodrug conjugate. The self‐assembled nanodrug possesses an increased intersystem crossing rate owing to the aggregation of dye, leading to a distinct singlet oxygen quantum yield (Φ( 1 O2 )). Subsequently, upon red light irradiation, the generated singlet oxygen reduces the size of the nanodrug from 90 to 10 nm, which facilitates deep tumor penetration of the nanodrug and release of chemodrug. The nanodrug achieved in situ tumor imaging and potent tumor inhibition by deep chemo‐PDT. Our work verifies a facile and effective self‐assembly strategy to construct nanodrugs with enhanced performance for cancer theranostics.